Current Issues of Antipyretic Therapy in Children with Acute Respiratory Infections - E. I. Novikova (Вопросы современной педиатрии)
This article discusses the current issues in the pediatric practice of seasonal incidence of children with acute respiratory infections. The basic etiological aspects of this pathology, specific clinical symptoms typical for different pathogens, causes of bursts of disease in certain periods are described. Special attention is paid to the tactics of antipyretic therapy in different groups of children with fever and acute respiratory diseases, understand the typical errors in its appointment. The author discusses the domestic and foreign results of using ibuprofen to relieve fever in children with this pathology, comparative efficacy and safety data of ibuprofen with other analgesics-antipyretics.